MODELING OF UTILITIES ECONOMY ON THE NATURE PRECIOUS AREAS - THE INSIGHT CHARACTERISTICS - BIEDRAWA, Agnieszka; SOBCZYK, Wiktoria (Trends in education, 2009)
Due to the act from 16 April 2004 the protection of nature means taking care of a balanced usage of nature resources. Its' aim is sustaining the existence of plant and animals species together with their habitations, through remaining and restoring them to the proper condition. For realisation of those aims we protect the recourses and elements of nature and the scientific research is conducted connected with their' protection. Our country is exposed to degradation and devastation of environment through the increasing number of utilities. The dangers are increasing from day to day with the increase of the number of population and development of industry. The subject of this particular article is the short characteristics of the protection of precious nature areas against the problems connected with utilities economy.
Keywords: Precious nature areas; utilities economy; models of limiting the dangers.